Future Earth—linking research on health and environmental sustainability. (1st June 2017) - Haines, Andy; Harris, Francesca; Kasuga, Fumiko; Machalaba, Catherine
Abstract : Andy Haines and colleagues describe how new research platforms present an opportunity to advance understanding of how to safeguard health in the face of global environmental change